1944
DOI: 10.1084/jem.80.6.521
|View full text |Cite
|
Sign up to set email alerts
|

The Sedimentation Rate of the Biological Activities of Influenza a Virus

Abstract: The sedimentation rates of the mouse infectivity principles of the PR8 and the F12 strains of influenza A virus were shown by studies in the separation cell to have values which are not significantly different from sedimentation rates of the principal components of purified preparations. It was shown further that the bulk of the chicken red blood cell agglutinating activity and of the chick embryo infectivity of PR8 influenza virus preparations sediments at the same rate as that of the 100 mµ. component. Some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1944
1944
1964
1964

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 15 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…The coincidence of optimum pH conditions for the two types of biological activity may be regarded as evidence that both activities arise from the same particle. Independent evidence obtained by means of centrifuge studies has provided more conclusive proof for the identification of the two properties with a single physical unit (17,18). The marked differences which have been observed between the rates of loss of CCA activity and of infectivity suggest, however, that the CCA activity is much less sensitive than the infectivity to alterations in virus structure.…”
Section: Discussionmentioning
confidence: 95%
“…The coincidence of optimum pH conditions for the two types of biological activity may be regarded as evidence that both activities arise from the same particle. Independent evidence obtained by means of centrifuge studies has provided more conclusive proof for the identification of the two properties with a single physical unit (17,18). The marked differences which have been observed between the rates of loss of CCA activity and of infectivity suggest, however, that the CCA activity is much less sensitive than the infectivity to alterations in virus structure.…”
Section: Discussionmentioning
confidence: 95%
“…In these experiments the virus was ultracentrifuged in a sucrose gradient made by adding successively· more dilute sucrose solutions, all con taining the same concentration of virus, to the centrifuge tube. In comparable experiments in a centrifuge cell fitted with a moveable partition Lauffer & Miller (20) found no difference between the sedi mentation constant of the infective and agglutinating principles. The discrepancy may be due to the different techniques or to differences in the initial degree of polydispersity in the virus preparations used by the three groups of workers.…”
Section: Influenza Virusesmentioning
confidence: 92%
“…From infectious allantoic fluid of chick embryos, highly purified preparations of PR8 influenza virus have recently been obtained which are homogeneous in the analytical ultracentrifuge and in the Tiselius electrophoresis apparatus and which consist of particles about 100 m/~ in diameter (9)(10)(11)(12)(13). When these particles are sedimented it can be shown that the units carrying infectivity and chick cell agglutinating activity sediment at the same rate (14). Therefore, from the association of biological activity with particles of uniform size and electrochemical behavior, it can be concluded, although possibly prematurely, that such particles represent influenza virus.…”
mentioning
confidence: 99%